Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/microorganisms11020378
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Metal and Metal Oxide Nanoparticles Using Microbial Cultures: Mechanisms, Antimicrobial Activity and Applications to Cultural Heritage

Abstract: Nanoparticles (1 to 100 nm) have unique physical and chemical properties, which makes them suitable for application in a vast range of scientific and technological fields. In particular, metal nanoparticle (MNPs) research has been showing promising antimicrobial activities, paving the way for new applications. However, despite some research into their antimicrobial potential, the antimicrobial mechanisms are still not well determined. Nanoparticles’ biosynthesis, using plant extracts or microorganisms, has sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 266 publications
0
5
0
Order By: Relevance
“…85,87,88 Finally, nanoscale materials like metal (or metal oxide) particles, nanocarriers, and inorganic-organic hybrids have been explored in the past few years to counteract microorganisms, corrosion, environmental pollutants (as acetic acid), and weathering, or to provide mechanical consolidation. Some examples include silver 89,90 or titanium dioxide nanoparticles, 91,92 and zinc oxide micro-or nanoparticles, [93][94][95] also embedded in polymer matrices, layered double hydroxides nanocarriers, 96 mesoporous silica nanoparticles, 97 halloysite nanotubes, 98,99 cellulose nanocrystals/fibrils or lignin nanoparticles, 100 cellulose-fibroin colloidal dispersions, 101 and starch nanoparticles. 102 These examples are representative of the potential that nanoscience and colloids have in the formulation of materials for the preservation of CH, with particular emphasis on bio-or biomimetic systems with enhanced properties and reduced ecotoxicity.…”
Section: Nanoscale Materials For Cultural Heritage Conservation -An O...mentioning
confidence: 99%
“…85,87,88 Finally, nanoscale materials like metal (or metal oxide) particles, nanocarriers, and inorganic-organic hybrids have been explored in the past few years to counteract microorganisms, corrosion, environmental pollutants (as acetic acid), and weathering, or to provide mechanical consolidation. Some examples include silver 89,90 or titanium dioxide nanoparticles, 91,92 and zinc oxide micro-or nanoparticles, [93][94][95] also embedded in polymer matrices, layered double hydroxides nanocarriers, 96 mesoporous silica nanoparticles, 97 halloysite nanotubes, 98,99 cellulose nanocrystals/fibrils or lignin nanoparticles, 100 cellulose-fibroin colloidal dispersions, 101 and starch nanoparticles. 102 These examples are representative of the potential that nanoscience and colloids have in the formulation of materials for the preservation of CH, with particular emphasis on bio-or biomimetic systems with enhanced properties and reduced ecotoxicity.…”
Section: Nanoscale Materials For Cultural Heritage Conservation -An O...mentioning
confidence: 99%
“…In terms of the antibacterial properties of the nanomaterials, the ability of the bacterial cells to regrow on the nutrient agar plates following their incubation on the MIC assay shows that the Cu-TiO 2 nanoparticles are bacteriostatic, and not bactericidal (i.e., they inhibit bacterial growth without killing the cells. , The clinical importance of bactericidal and bacteriostatic samples, however, is still under dispute and is not used to rule out the potential application of samples as antimicrobial agents. In general, the results in Figure a,b have shown that no significant differences in the antimicrobial activity of the TiO 2 nanoparticles were observed in the presence and the absence of copper.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of metal NPs using bacteria has been described in most detail in ref 83. Bacteria can synthesize Mn NPs in two ways: intracellular and extracellular.…”
Section: Using Microorganisms (Bacteria Microscopic Fungi and Virusesmentioning
confidence: 99%